I Love My Cat With The Very Hungry Caterpillar - Carle, Eric; Carle, Eric ([Place of publication not identified] : World of Eric Carle, 2025)
Celebrate the bond between cat lovers and their cats with the Very Hungry Caterpillar! Complete with Eric Carle's classic joyful illustrations and featuring his favorite animal, this charming keepsake is a great way to celebrate cherished pets and show the cat lovers in your life how much you care!
new kids book 2025 fall.
Keywords: Animals; Cats; love and romance